An Update on the Family Educational Rights and Privacy Act. Issue 172 (9th June 2017) - Fuller, Matthew
Abstract : Despite its prominence, the Family Educational Rights and Privacy Act (FERPA) is often misinterpreted and misapplied. This chapter clarifies historical developments, common misconceptions, and modern applications of the law.